Carbon Pricing: A Comparison between Germany and the United Kingdom - Karina Temoche González (Junior Management Science (JUMS), 2022)
Climate change is a global problem that almost every country – 191 parties had signed the Paris Agreement - has committed to undertake. The European Union (EU) has been one of the pioneers in implementing policies that tackle greenhouse gas emissions (GHG). In 2005, the European Emissions Trading Scheme (EU ETS) was launched as the first carbon market. Despite the EU ETS evolving throughout the years, the United Kingdom (UK) implemented an additional policy. In 2013, the UK introduced a Carbon Price Floor (CPF). This paper examines the impact of carbon pricing on GHG emissions during phase III of the EU ETS (2017-2020) in Germany and the UK. Electricity generated by nuclear and renewable sources are considered in the analysis. There are two research questions. First, is the impact of carbon pricing in these two countries, measured by using an Ordinary Least Squares (OLS) model for panel data. The results show that the UK has been more successful in reducing GHG emissions because of the CPF implementation. Second, whether the Market Stability Reserve (MSR) – a policy within the EU ETS – acted as a Carbon Price Floor (CPF) for Germany. Using a model of Differences in Differences (DD), this paper showed that the MSR significantly reduced the CO2 emissions of Germany.
Keywords: 650; Carbon price; EU ETS; CO2 emissions; carbon price floor; market stability reserve; differences in differences